Implementasi Pendidikan Soft Skills dalam Membentuk Moralitas Siswa di Madrasah Aliyah Negeri Bangkalan - Husairi Husairi; Lutfi Rachman (Al-Jadwa: Jurnal Studi Islam, 2021)
ABSTRACT The education is called as student character development process so that students have the knowledge (cognitive), attitudes (affective) and skills (psychomotor) for the provision of living the midst of society. This process involves improvement the intellectual, personal and social skills are balanced between hard skills and soft skills that are not only useful for himself (intrapersonal skills) but also beneficial to the existence of society (interpersonal skills). Soft skills are a core part of non-technical competencies that are specifically able to refer to personality characteristics. These competencies are seen in a person's behavior, starting when interacting with the social environment, language skills, personal habits, to important traits aimed at supporting optimistic behavior in all fields. The characteristics of the educational model of soft skills in forming morality of students in Madrasah Aliyah Negeri Bangkalan that is using a model of "integration" model is an intermingling between hard skills and soft skills and connects all general subjects by incorporating values of Islam so that it becomes unified whole. Implementation of educational soft skills in order to form the morality of students by means of: 1) Planting moral values through learning integtatif, 2) Cooperate with the unit institutions Madrasah Aliyah Negeri Bangkalan, 3) To collaborate with parents, 4) Through practice approach and methods of demonstration, 5) approach through habituation, 6) Planting moral values through counseling, 7) Planting of moral values through obedience approach, 8) Planting moral values with religious extracurricular activities. Implications of soft skills in forming moral of students in Madrasah Aliyah Negeri Bangkalan, among others: (1) Form of Spiritual (faith and devotion to Allah) indicators: (a) Implement Duha prayer at recess and familiarize prayer duhur congregation (b) Students should shake hands when meet with teachers, especially in the time to come to school and when the school or at the time outside of school (c) civilize a greeting, greet and smile when dealing with others both in the classroom and outside the classroom. (2) The form of integrity/honesty and (3) The form of discipline and self-awareness. Keywords: Soft Skills Education, Student Morality